Laccase Directed Lignification Is One of the Major Processes Associated With the Defense Response Against Pythium ultimum Infection in Apple Roots - Zhu, Yanmin; Li, Guanliang; Singh, Jugpreet; Khan, Awais; Fazio, Gennaro; Saltzgiver, Melody; Xia, Rui (Frontiers in Plant Science, 2021)
Apple replant disease (ARD), incited by a pathogen complex including Pythium ultimum, causes stunted growth or death of newly planted trees at replant sites. Development and deployment of resistant or tolerant rootstocks offers a cost-effective, ecologically friendly, and durable approach for ARD management. Maximized exploitation of natural resistance requires integrated efforts to identify key regulatory mechanisms underlying resistance traits in apple. In this study, miRNA profiling and degradome sequencing identified major miRNA pathways and candidate genes using six apple rootstock genotypes with contrasting phenotypes to P. ultimum infection. The comprehensive RNA-seq dataset offered an expansive view of post-transcriptional regulation of apple root defense activation in response to infection from P. ultimum. Several pairs of miRNA families and their corresponding targets were identified for their roles in defense response in apple roots, including miR397-laccase, miR398-superoxide dismutase, miR10986-polyphenol oxidase, miR482-resistance genes, and miR160-auxin response factor. Of these families, the genotype-specific expression patterns of miR397 indicated its fundamental role in developing defense response patterns to P. ultimum infection. Combined with other identified copper proteins, the importance of cellular fortification, such as lignification of root tissues by the action of laccase, may critically contribute to genotype-specific resistance traits. Our findings suggest that quick and enhanced lignification of apple roots may significantly impede pathogen penetration and minimize the disruption of effective defense activation in roots of resistant genotypes. The identified target miRNA species and target genes consist of a valuable resource for subsequent functional analysis of their roles during interaction between apple roots and P. ultimum.